A proteomics approach to identifying novel protein targets involved in erinacine A–mediated inhibition of colorectal cancer cells' aggressiveness. Issue 3 (6th October 2016) - Lee, Ko‐Chao; Kuo, Hsing‐Chun; Shen, Chien‐Heng; Lu, Chien‐Chang; Huang, Wen‐Shih; Hsieh, Meng‐Chiao; Huang, Cheng‐Yi; Kuo, Yi‐Hung; Hsieh, Yung‐Yu; Teng, Chih‐Chuan; Lee, Li‐Ya; Tung, Shui‐Yi
Abstract: Erinacine A, a major active component of a diterpenoid derivative isolated from Hericium erinaceus mycelium, has been demonstrated to exert anticancer effects. Herein, we present an investigation of the molecular mechanism of erinacine A induction associated with cancer cells' aggressive status and death. A proteomic approach was used to purify and identify the differentially expressed proteins following erinacine A treatment and the mechanism of its action in apoptotic and the targets of erinacine A. Our results demonstrate that erinacine A treatment of HCT‐116 and DLD‐1 cells increased cell cytotoxicity and reactive oxygen species (ROS) production as well as decreased cell proliferation and invasiveness. Ten differentially displayed proteins were determined and validated in vitro and in vivo between the erinacine A‐treated and untreated groups. In addition, erinacine A time‐dependent induction of cell death and inhibitory invasiveness was associated with sustained phosphorylation of the PI3K/mTOR/p70S6K and ROCK1/LIMK2/Cofilin pathways. Furthermore, we demonstrated that erinacine A–induced HCT‐116 and DLD‐1 cells viability and anti‐invasion properties by up‐regulating the activation of PI3K/mTOR/p70S6K and production of ROS. Experiments involving specific inhibitors demonstrated that the differential expression of cofilin‐1 (COFL1) and profilin‐1 (PROF1) during erinacine A treatment could be involved in the mechanisms of HCT‐116 and DLD‐1 cells death and decreased aggressiveness, which occurred via ROCK1/LIMK2/Cofilin expression, with activation of the PI3K/mTOR/p70S6K signalling pathway. These findings elucidate the mechanism of erinacine A inhibiting the aggressive status of cells by activating PI3K/mTOR/p70S6K downstream signalling and the novel protein targets COF1 and PROF1; this could be a good molecular strategy to limit the aggressiveness of CRC cells.